SOUTH KOREA IN THE DYNAMICS OF INDO-PACIFIC STRATEGY: HERMIT KINGDOM 4.0 [KOREA SELATAN PADA DINAMIKA STRATEGI INDO-PASIFIK: KERAJAAN HERMIT 4.0] - Darynaufal Mulyaman; William Sulistyo Wibowo (Universitas Pelita Harapan, 2021)
South Korea is a country that historically has always been flanked by major powers around it such as Japan, China, Russia, and even the United States. Nevertheless, South Korea in this era of globalization actually has a large capacity as a middle power country engaged by influential multilateral organizations such as the OECD, MIKTA, and G20. Later, South Korea also had huge popular culture implications around the world through its Korean Wave. So why is South Korea less politically active on Indo-Pacific issues than other East Asian countries, such as Japan with the Quad or China in the Indo-Pacific issue? Whereas by weight of issue and substance, South Korea has a big point to play strategically on Indo-Pacific dynamics issues, such as the North Korea issue or the Alliance of South Korea and the United States. The study will use Economic Diplomacy and Middle-power-ship to explain the reasons why South Korea tends to be politically inactive. Bahasa Indonesia Abstract: Korea Selatan merupakan negara yang secara historis selalu diapit oleh kekuatan besar di sekitarnya seperti Jepang, China, Rusia, bahkan Amerika Serikat. Namun demikian, Korea Selatan di era globalisasi ini sebenarnya memiliki kapasitas yang besar sebagai middle power country yang digaet oleh organisasi multilateral berpengaruh seperti OECD, MIKTA, dan G20. Belakangan, Korea Selatan juga memiliki implikasi budaya populer yang sangat besar di seluruh dunia melalui Korean Wave-nya. Jadi mengapa Korea Selatan kurang aktif secara politik dalam isu-isu Indo-Pasifik dibandingkan negara-negara Asia Timur lainnya, seperti Jepang dengan Quad atau China dalam masalah Indo-Pasifik? Padahal secara bobot isu dan substansi, Korea Selatan memiliki poin besar untuk bermain secara strategis pada isu-isu dinamika Indo-Pasifik, seperti isu Korea Utara atau Aliansi Korea Selatan dan Amerika Serikat. Studi ini akan menggunakan Diplomasi Ekonomi dan Middle-power untuk menjelaskan alasan mengapa Korea Selatan cenderung tidak aktif secara politik.